BACK TO THE FUTURE: POSTNARRATIVIST HISTORIOGRAPHY AND ANALYTIC PHILOSOPHY OF HISTORY1. Issue 2 (May 2016) - Roth, Paul A.
ABSTRACT: Jouni‐Matti Kuukkanen has written an important book. It directly confronts a key theoretical dilemma that has shadowed debate in historiography for several decades: histories cannot be written without using some narrative structure or other, but epistemological evaluation cannot be applied to narratives qua narrative. Thus, if empirical inquiry takes the form of a history, then it cannot be rationally evaluable, and if rationally evaluable, empirical inquiry cannot be in the form of a history. Kuukkanen's book both directly confronts and proposes a strategy for surmounting this tired and tiresome theoretical barrier. Kuukkanen deserves great credit for attempting to reshape a long‐stalled debate in a way that enables the theoretical options to be imagined anew. Yet his structuring of the oppositional tendencies engenders some ongoing problems regarding how to understand the philosophical stakes and options. This review argues that achieving Kuukkanen's postnarrativist future requires going back to past epistemic concerns discarded because they were tied to conceptions of logic and explanation that could not be reconciled with narrative form. Kuukkanen practices postnarrativism but still preaches a prenarrativist conception of logic. To reach his promised future, to actually overcome the dilemma that he rightly seeks to transcend, one must actually have the courage of Kuukkanen's pragmatist convictions.